Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Bengkel Indah Jaya Motor Di Sragen - Gimantoro, Asadha Mercuri, Drs. Widoyono, M.M (2015)
The purpose of this study was to determine the effect of service quality consisting of Reability, responssive, assurance, empathy, and tangible significantly to customer satisfaction wonderful workshop victorious in Sragen and to determine which variables are the most dominant influence on consumer satisfaction garage Indah Jaya in Sragen. The sample used in this study of 100 respondents, while sampling was conducted on consumers who use the services Indah Jaya motorcycle repair shop in Sragen by using Simple Random Sampling. The analytical tool used to determine the influence of service quality to customer satisfaction using data analysis tools Test Validity and Reliability Test, Classical Assumption Test, Multiple Regression, t test, F test and coefficient of determination. Based on the analysis found that the variable t test, reliability (4.031> 2.000), responsiveness (2,225> 2,000), assurance (2,338> 2,000), empathy (2,234> 2,000), and tangible (2,195> 2,000) has a positive and significant impact on the consumer satisfaction in workshop Indah Jaya Motor in Sragen. F-test analysis results are used to determine the influence of variables Reliability (X1), Responsive (X2), Assurance (X3), Empathy (X4), and Tangibles (X5) jointly against Consumer satisfaction (Y) and the coefficient of determination (R2) obtained R square (R2) of 0.567, meaning variation satisfaction variables can change dijelskan by variable reliability (X1), responsiveness (X2), Assurance (X3), Empathy (X4), and tangible (X5) 56.7 %. While the remaining 43.3% is explained by other variables outside the model. Thus the hypothesis proposed in this study that variable reliability (reliability) of the most dominant influence on consumer satisfaction garage Indah Jaya in Sragen proven true, to prove that tcount reliability of 4.031, responsive amounted to 2,225, assurance amounted to 2.338, 2.234 and empathy for tangible amounted to 2,195.